PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BAHAN BAKU NAYZ DI PT. MITRA KERJA NAYZ - Asmar Shiddiq Autarki; Ahmad Nurhadi (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine whether Product Quality and Price have a good influence, either partially or simultaneously, on Purchasing Decisions on Nayz Raw Materials at PT. Mitra Kerja Nayz. The research method uses a quantitative method with a sample of 94 respondents. The data feasibility test uses a validity test, reliability test and classical assumption test. The data analysis technique uses a simple linear regression test, multiple linear regression test, determination test and hypothesis test. The results of the study show that product quality (X1) and price (X2) have a positive and significant effect on purchasing decisions with the regression equation Y = 8.645 + 0.409X1 + 0.388X2. The results of this regression analysis show that the coefficient of each variable is positive, meaning that the higher the product quality and price, the higher the purchasing decision. While the correlation value or level of influence between the independent variable and the dependent variable is obtained at 0.702, meaning it has a strong influence, the determination value or contribution of the influence of product quality and price simultaneously is 60.9% while the remaining 39.1% is influenced by other factors. Hypothesis testing obtained a value of T count> T table 5.203> 1.986) with a significant level of 0.000 <0.05, it can be concluded that Ho is rejected and H1 is accepted. This means that there is a positive and significant partial influence between product quality and purchasing decisions, T count> T table (5.167> 1.986) with a significant value of 0.000 <0.05, it can be concluded that Ho is rejected and H2 is accepted. This means that there is a positive and significant partial influence between price on purchasing decisions and F count> F table (70.772> 3.10) this is also reinforced by a probability significance of 0.000 <0.05. Thus Ho is rejected and H3 is accepted. This means that there is a positive and significant influence simultaneously between the variables of product quality and price on the purchasing decision of Nayz Raw Materials at PT. Mitra Kerja Nayz.